A second gene for autosomal dominant Möbius syndrome is localized to chromosome 10q, in a Dutch family. - Verzijl, H T (1999)
Möbius syndrome (MIM 157900) consists of a congenital paresis or paralysis of the VIIth (facial) cranial nerve, frequently accompanied by dysfunction of other cranial nerves. The abducens nerve is typically affected, and often, also, the hypoglossal nerve. In addition, orofacial and limb malformations, defects of the musculoskeletal system, and mental retardation are seen in patients with Möbius syndrome. Most cases are sporadic, but familial recurrence can occur. Different modes of inheritance are suggested by different pedigrees. Genetic heterogeneity of Möbius syndrome has been suggested by cytogenetic studies and linkage analysis. Previously, we identified a locus on chromosome 3q21-22, in a large Dutch family with Möbius syndrome consisting essentially of autosomal dominant asymmetric bilateral facial paresis. Here we report linkage analysis in a second large Dutch family with autosomal dominant inherited facial paresis. After exclusion of >90% of the genome, we identified the locus on the long arm of chromosome 10 in this family, demonstrating genetic heterogeneity of this condition. The reduced penetrance suggests that at least some of the sporadic cases might be familial.